2008
DOI: 10.1016/j.cbi.2007.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Changing ratios of omega-6 to omega-3 fatty acids can differentially modulate polychlorinated biphenyl toxicity in endothelial cells

Abstract: Exposure to persistent organic pollutants, such as polychlorinated biphenyls (PCBs) can cause endothelial cell (EC) activation by inducing pro-inflammatory signaling pathways. Our previous studies indicated that linoleic acid (LA, 18:2), a major omega-6 unsaturated fatty acid in the American diet, can potentiate PCB77-mediated inflammatory responses in EC. In addition, omega-3 fatty acids (such as α-linolenic acid, ALA, 18:3) are known for their anti-inflammatory properties. We tested the hypothesis that mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…In this respect, in a recent study, Alegría-Torres et al (Frigo et al, 2004;Kim et al, 2004). Similar findings were found for PCBs (Bezdecny et al, 2007;Glauert et al, 2008;Myhre et al, 2009;Wang et al, 2008). In line with the mechanism proposed by Champion et al (2013), our data showed that the over-expression of AhR was dependent on the TNF induced by DDE and PCB 153.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this respect, in a recent study, Alegría-Torres et al (Frigo et al, 2004;Kim et al, 2004). Similar findings were found for PCBs (Bezdecny et al, 2007;Glauert et al, 2008;Myhre et al, 2009;Wang et al, 2008). In line with the mechanism proposed by Champion et al (2013), our data showed that the over-expression of AhR was dependent on the TNF induced by DDE and PCB 153.…”
Section: Discussionsupporting
confidence: 91%
“…Those findings indicated that AhR expression in FLSs was stimulated in the presence of TNF, similar to our results here. Taking into account that data and our own, we hypothesize that TNF induced by DDE and PCB 153 (Alegría-Torres et al 2009; Cárdenas-González et al, 2013), likely via an NF-B pathway (Bezdecny et al, 2007;Frigo et al, 2004;Glauert et al, 2008;Kim et al, 2004;Myhre et al, 2009;Wang et al, 2008), was able to induce AhR mRNA expression.…”
Section: Discussionmentioning
confidence: 62%
“…cultured hepatocytes (Palanisamy et al, 2015;Turkez et al, 2011b) and that a higher ratio of n-3/n-6 PUFAs can reduce oxidative stress and inflammation induced by the dioxin-like polychlorinated biphenyl, PCB77, in cultured endothelial cells (Wang et al, 2008). Additionally, both EPA and DHA protect against TCDD-induced oxidative stress and hepatic and renal injury in rats in vivo (Palaniswamy et al, 2014;Turkez et al, 2011a).…”
Section: Discussionmentioning
confidence: 99%
“…The uptake of polychlorinated biphenyls (PCBs) by endothelial cells has been shown to be increased in the presence of linoleic acid (141), and it has been suggested that PCBs activate endothelial cells by mechanisms involving caveolae (90). It is possible that PCBs accumulate in the caveolae of endothelial cells and somehow interact with specific fatty acids since linoleic acid amplified, whereas α-linolenic acid protected against, PCB-induced endothelial activation (159,164). Oily fish containing longchain n-3 PUFAs could potentially be contaminated with organic pollutants and thus represent a food group that has substantial health benefits as well as possible risks (59).…”
Section: Fatty Acids Lipid Rafts and Environmental Toxicity In Endomentioning
confidence: 99%